Impact of cortical mastoidectomy on tympanoplasty for recurrent suppurative otitis media: a prospective study - Sisodia, Shalini Singh; Sriprakash, Vinnakota (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic suppurative otitis media condition is characterized by an ear discharge and a perforation in the tympanic membrane. Tympanoplasty and tympanoplasty with mastoidectomy are the two common surgeries performed to manage this condition. Methods: 50 patients were divided into two groups of 25 each. On Group I, tympanoplasty alone was done and on Group II tympanoplasty along with mastoidectomy was performed and outcome was noted. Results: The most common age group to be affected was 21-30 years. Discharge of 1-3 years was observed in 32% in Group I and 36% in Group II. 84% in Group I and 72% in Group II had mild hearing loss, and in both the groups, moderate perforations were more common. 84% of the patients in Group I and 88% in group II showed acceptance to the surgeries and the hearing gain in both the groups was around 10. Conclusions: This study shows that tympanoplasty with mastoidectomy has no added advantage over tympanoplasty alone in the patients with chronic suppurative otitis media.